Numerical assessment of frp retrofitting systems for reinforced concrete elements - Rougier,Viviana Carolina (2007)
During their service life reinforced concrete structures can be exposed to mechanical loads and aggressive chemical or thermal agents that produce degradation of their mechanical properties. This results in a loss of security and usually requires a prompt repair or retrofitting in order to preserve the structural serviceability. In this case, the aid of a numerical tool for the assessment of different retrofit and repair systems would be valuable. Nowadays, analytical and numerical capacity for the assessment of this type of systems is still limited. A numerical model that can be used for the assessment of retrofit and repair systems based on the use of FRP for reinforced concrete columns and beams is presented in this paper. A plastic damaged model that reproduces the behaviour even under high confinement pressures is used for concrete. Application examples concerning the behaviour of reinforced concrete columns and beams retrofitted with FRP are included in the paper. The comparison with experimental results shows the ability of the proposed model to reproduce the problem simulated.